Probing the Structural Details of Chitin Nanocrystal–Water Interfaces by Three‐Dimensional Atomic Force Microscopy (Small Methods 9/2022). Issue 9 (19th September 2022) - Yurtsever, Ayhan; Wang, Pei‐Xi; Priante, Fabio; Morais Jaques, Ygor; Miyata, Kazuki; MacLachlan, Mark J.; Foster, Adam S.; Fukuma, Takeshi
Abstract : Chitin Nanocrystal Structure In article number 2200320, Yurtsever, Fukuma, and co‐workers provided the molecular‐scale structural details of chitin nanocrystals in water by combining 3D atomic force microscopy experiments and molecular dynamics simulations. The characterization of chitin nanocrystal surfaces at the molecular scale could pave the way for assessing the chemical and enzymatic activities on chitin nanocrystals, offering an understanding of the mechanisms of chitin degradation.